ANALISIS MODEL BISNIS BURGERKUY DENGAN PENDEKATAN BUSINESS MODEL CANVAS - Irvan Kurniawan; Asni Harianti (Universitas YPPI Rembang, 2023)
Large-Scale Social Restrictions (PSBB) due to the COVID-19 pandemic have an impact on activities in various public facilities, such as restaurants, malls, tourist attractions, and so on. This situation causes people to choose to buy food online through social media. BURGERKUY was founded because of the online business opportunity. BURGERKUY is a business that sells burgers with a distinctive taste and changes people's mindset because the product uses chicken and fish as a substitute for bread. This study aims to analyze the BURGERKUY business model using the business model canvas. This research method uses descriptive qualitative research with data collection techniques in the form of observation and interviews. The results of this study are in the form of evaluating the results of SWOT analysis on nine elements of the canvas business model which provide recommendations for improvements to the element's value proposition by adding flavor variants and adding new variant toppings, channels for having outlets in Pekanbaru, customer relations for holding promos and participating in culinary events for attracting consumers to buy, the main activity is to control the product, the main partnership to work with food bloggers or food reviewers from Pekanbaru, the revenue stream to open a franchise in Pekanbaru.